Accidents at construction site: who bears the liability? / Abdul Haris Nawi, Nurfarizan Tumin and Sharifuddin Liwan - Nawi, Abdul Haris; Tumin, Nurfarizan; Liwan, Sharifuddin (2006)
Rapid development of Malaysian construction industry is plaque with industrial accidents! Whether we realize it or not, the numbers of accidents in construction site has increased. The need for a greater development project is compensated with injuries and lost of lives of the innocent that pull all their strength to make our homes a batter home. That is the reality and danger that the workers are facing day by day. The sad story does not stop there, it affect the public too. This happens when the victim is the member of the public who were happened to be at the site. Accident struck! The issues here is, whether the society realize the threat? This phenomena needs to be curbed in order maintain the safety of these innocent people. Thus promoting better safety and prevention method would invade accidents at construction site.